High-resolution synchrotron imaging shows that root hairs influence rhizosphere soil structure formation - Koebernick, Nicolai; Daly, Keith R.; Keyes, Samuel D.; George, Timothy S.; Brown, Lawrie K.; Raffan, Annette; Cooper, Laura J.; Naveed, Muhammad; Bengough, Anthony G.; Sinclair, Ian; Hallett, Paul D.; Roose, Tiina (The New phytologist, 2017)
In this paper, we provide direct evidence of the importance of root hairs on pore structure development at the root–soil interface during the early stage of crop establishment. This was achieved by use of high-resolution (c. 5 μm) synchrotron radiation computed tomography (SRCT) to visualise both the structure of root hairs and the soil pore structure in plant–soil microcosms. Two contrasting genotypes of barley (Hordeum vulgare), with and without root hairs, were grown for 8d in microcosms packed with sandy loam soil at 1.2 g cm−3 dry bulk density. Root hairs were visualised within air-filled pore spaces, but not in the fine-textured soil regions. We found that the genotype with root hairs significantly altered the porosity and connectivity of the detectable pore space (> 5 μm) in the rhizosphere, as compared with the no-hair mutants. Both genotypes showed decreasing pore space between 0.8 and 0.1mm from the root surface. Interestingly the root-hair-bearing genotype had a significantly greater soil pore volume-fraction at the root–soil interface. Effects of pore structure on diffusion and permeability were estimated to be functionally insignificant under saturated conditions when simulated using image-based modelling.